Chemicals Applied in Fall and Defoliation on Dormancy Evolution and Release in Low-chill Peach ‘Flordaking’ - Gariglio, Norberto Francisco (2012)
The aim of this work was to study the effect of fall defoliation and chemical application on the progression and release of dormancy, and phenology, of low-chill peach ‘Flordaking’ under temperate climate conditions. At the onset of leaf fall, ‘Flordaking’ peach (Prunus persica L. Batsch) trees were defoliated or treated with hydrogen cyanamide (2.5 g L-1 a.i), norflurazon (46 g L-1 a.i.) or ethephon (20 mg L-1 a.i.). Untreated trees were used as the control. The rate of budbreak and the mean time to budbreak (MTB) was tested on stem isolates in a phytotron, whereas tree phenology and vegetative and reproductive traits were evaluated in a field experiment. Defoliation and chemical treatments significantly affected the rate of budbreak evolution of floral, but not of vegetative, buds. Treatments also significantly affected the evolution of the MTB of both vegetative and floral buds, but with a greater effect on the latter. In the field, the phenology of Flordaking was more affected by treatments that modified the depth of dormancy than those which affected the percentage of budbreak in excised shoots. Defoliation and hydrogen cyanamide treatments advanced sprouting (15 and ten days, respectively) and blooming (16 and four days, respectively), whereas ethephon delayed flowering and fruit set by three days each. Fall defoliation at the beginning of leaf abscission appears to be a strong tool to manipulate the evolution of dormancy and the time of spring bloom of Flordaking, mainly when insufficient chilling accumulation is forecasted.